Characterization of cytotoxic and genotoxic effects of contaminated sediments from the Sado Estuary and potential human health risk - Pinto, Miguel (2012)
The river Sado Estuary (W Portugal) is affected by various sources of pollution, such as heavy-industry, urbanism, mining, agriculture and maritime traffic. Mostly classified as a natural reserve, it also remains a privileged site for fishing activities performed by the local population, who not only consume but distribute their fishery. The present study is part of a broader project whose objective is to evaluate the environmental and human health risks associated with the estuarine benthic environment. This study aims to assess the cytotoxic and genotoxic potential of sediments from several local fishing areas of the Sado Estuary. Sediments were collected from four geochemically distinct and potentially contaminated sites of the Sado Estuary: sites C and P from the northern shore and sites E and A from the southern shore. A previously characterized sample (F) from the northern shore was added as a positive control. Total organic and inorganic contaminants were extracted with a mixture of methanol:dichloromethane (1:2) and recovered in DMSO. Cytotoxicity and genotoxicity were evaluated through the neutral red uptake assay and by the alkaline comet (coupled with DNA repair endonucleases) and the micronucleus assays, respectively, in the human HepG2 cell line. Cells were exposed for 48h to concentrations of each extract ranging from 0.1 to 20µl/ml of culture medium. A dose-related decrease in cell viability was observed for extracts F, P and E, indicating sediment contaminant-driven cytotoxicity, whereas no effect was observed for extracts C and A. No significant genotoxicity was observed for extract C, while extract F was clearly genotoxic, as expected. A significant increase in the level of DNA and chromosome damage was observed, by the comet and micronucleus assays, respectively, for sub cytotoxic concentrations of extracts P and E. The level of DNA damage was accentuated following treatment with the DNA repair endonuclease FPG, suggesting the existence of oxidative DNA damage. Extract A was genotoxic in the micronucleus assay and in the comet assay only after FPG treatment. Negative results from sample C leads us to consider it as potential clean reference for further studies. Moreover, sediment contamination analysis revealed high levels of metals in all samples except C, whereas only sample P exhibited high levels of known genotoxic polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and DDTs, similar to the previously described for sample F. The differential cytotoxicity and genotoxicity observed in samples from the northern (P) and southern areas (E and A) of the Sado Estuary probably reflects different pressures from a urban and heavy industrialized area versus an intense agricultural area, respectively. The observation that sediment samples have cytotoxic and genotoxic effects, together with the knowledge that contaminants can be accumulated in the edible parts of estuarine species or local agricultural products entering the human food chain, raise concern about a hazardous impact on the health of exposed populations that must be assessed. Work supported by the Foundation for Science and Technology (ref. PTDC/SAU-ESA/100107/2008).